2020
DOI: 10.3389/fmicb.2020.01998
|View full text |Cite
|
Sign up to set email alerts
|

Clostridioides difficile Toxin A-Induced Wnt/β-Catenin Pathway Inhibition Is Mediated by Rac1 Glucosylation

Abstract: Clostridioides difficile toxin A (TcdA) has been shown to inhibit cellular Wnt signaling, the major driving force behind the proliferation of epithelial cells in colonic crypts, likely through the inhibition of β-catenin nuclear translocation. Herein, we aimed to advance the understanding of this mechanism by replicating the findings in vivo and by investigating the specific role of Rac1, a member of the Rho GTPase family, on the inhibition of the Wnt-induced β-catenin nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Furthermore, the related TcdA has been shown to suppress Cyclin D1 expression ( Bezerra Lima et al, 2014 ). Interestingly, TcdA-induced inhibition of the Wnt/β-Catenin Pathway is shown to be preserved upon expression of non-glucosylatable Rac1-Q61L ( Martins et al, 2020 ). In sum, Rac1 seems to be the critical upstream regulator of G1 phase Cyclins on the level of Rho GTPases, which glucosylation by either TcdA or TcdB results in Cyclin D1 suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the related TcdA has been shown to suppress Cyclin D1 expression ( Bezerra Lima et al, 2014 ). Interestingly, TcdA-induced inhibition of the Wnt/β-Catenin Pathway is shown to be preserved upon expression of non-glucosylatable Rac1-Q61L ( Martins et al, 2020 ). In sum, Rac1 seems to be the critical upstream regulator of G1 phase Cyclins on the level of Rho GTPases, which glucosylation by either TcdA or TcdB results in Cyclin D1 suppression.…”
Section: Discussionmentioning
confidence: 99%
“…The signs and symptoms following CDI are influenced by various virulence factors, including the production of toxins and surface proteins [ 3 , 9 , 24 ]. The pathogenesis is primarily driven by the activity of toxins A and B, encoded in the pathogenicity locus of the C. difficile genome [ 25 , 26 ].…”
Section: Overview Of C Difficile ’S Toxinsmentioning
confidence: 99%
“…To date, there is no in vivo demonstration of cellular senescence during CDI, although studies on the effects of Tcds in the tissue of mice during CDI demonstrated changes in the expression of cell cycle inhibitors and CDKIs indicative of cell cycle arrest [24,25], strongly suggesting that cellular senescence could occur during CDI in vivo.…”
Section: Mechanisms Of Cellular Senescence Induced By Tcdbmentioning
confidence: 99%